Próba wykorzystania prognoz kombinowanych w prognozowaniu przychodów ze sprzedaży na przykładzie wybranej spółki giełdowej - Batóg, Barbara (The Trial of Application of Combination of Forecasts in Forecasting of Sales Revenue for One of Firm from Warsaw Stock Exchange, 2006)
In the paper the author constructed the combination of forecast for quarterly sales revenue for one of firm from Warsaw Stock Exchange. Individual forecasts were prepared on the basis of additive Holt-Winters model, linear trend with seasonality and harmonic analysis. It turned out that combination of forecasts was related to the percentage errors smaller than for every individual forecast. It was also pointed out that wages of combination should be calculated on the basis of possibly newest data.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1112, s. 168-176